Petrochronologic perspective on rhyolite volcano unrest at Laguna del Maule, Chile - Andersen, Nathan L. (2018)
Rhyolitic magmas have rarely erupted during historical times, thus we have a poor record of the signals of unrest that precede them. The Laguna del Maule volcanic field (LdM), Chile, is in the midst of a decade-long episode of unrest including surface inflation at more than 200 mm/yr. Geomorphic observations indicate that many similar deformation episodes occurred during the late Pleistocene and Holocene. During this time, approximately 40 km3 of rhyolite has erupted effusively and explosively from at least 24 vents distributed around a 300 km2 lake basin. The large volume, protracted eruptive history, and ongoing unrest of LdM offer an unusual opportunity to integrate petrologic reconstructions of recent rhyolite generation with geophysical and geodetic observations associated with an active, growing magma reservoir. New petrochronologic data shows that the most recent rhyolites, erupted during the last 3200 yr, each resided in the shallow crust for only decades following extraction from an underlying reservoir. The rhyolites contain only limited, cryptic evidence for magma replenishment and reheating in the form of Ba concentration spikes in plagioclase, which suggest biotite breakdown in a crystal-rich mush. The absence of evidence for substantial reheating or mixing with intruding magma preceding the rhyolitic eruptions indicates that they must have been triggered by another process. We propose the accumulation of fluids derived from the deeper degassing of mafic melts is capable of pressurizing eruptible magma bodies of low density rhyolite. This process likely continues to this day and is consistent with the best-fit models of the ongoing unrest. The striking absence of visible surface degassing accompanying the unrest at LdM suggests fluids are trapped beneath an impermeable carapace and could catalyze a future explosive eruption.